KNOWLEDGE MAP OF INFORMATION SCIENCE: IMPLICATIONS FOR THE FUTURE OF THE FIELD - Donald H. Kraft; Glynn Harmon; Nicolae Dragulanescu; Gordana Dodig-Crnkovic; Charles H. Davis; Michael Buckland; Clare Beghtol; Anthony Debons; Chaim Zins; Roberto Poli; Richard P. Smiraglia (Brazilian Journal of Information Science, 2007)
This collective paper incorporates eleven position papers on implications of the "Knowledge Map of Information Science,” a Critical Delphi study conducted in 2003-2005 and published as a series of four articles (ZINS, 2007 a, b, c, d). The Delphi study captured the deliberations of 57 leading information science scholars from 16 countries to provide (1) definitions of the fundamental concepts of data, information knowledge and message, (2) alternative conceptions of the broad information science domain, (3) different classificatory mappings of the field, and (4) comprehensive mappings of information science. Overall, the Knowledge Map provides an early 21st century snapshot of the field that should help guide future research, educational programming, publishing, and other professional and scholarly thrusts. Future information science mapping research should be done periodically, including additional Delphi studies and assessments of the degree of the field’s expansion and probable division into sub-fields. Alternative methodologies for mapping the expanding information science universe and its synergies with other fields of knowledge should also be explored.